Adenomyoepithelioma with Ductal Carcinoma In Situ: A Case Report and Review of the Literature. (25th February 2013) - Warrier, Sanjay; Hwang, Sang; Ghaly, Martha; Matthews, Alex
Abstract : Adenomyoepithelioma (AME) with microglandular adenosis-like growth pattern and superimposed ductal carcinoma in situ (DCIS) was identified in a 55-year-old female after biopsy of an atypical lesion identified through routine breast screening. A literature review reveals that this association has rarely been described.